Visible Discrimination of Broadband Infrared Light by Dye-Enhanced Upconversion in Lanthanide-Doped Nanocrystals - Charles G. Dupuy; Thomas L. Allen; George M. Williams; David Schut (Journal of Nanotechnology)
Optical upconversion of near infrared light to visible light is an attractive way to capture the optical energy or optical information contained in low-energy photons that is otherwise lost to the human eye or to certain photodetectors and solar cells. Until the recent application of broadband absorbing optical antennas, upconversion efficiency in lanthanide-doped nanocrystals was limited by the weak, narrow atomic absorption of a handful of sensitizer elements. In this work, we extend the role of the optical antenna to provide false-color, visible discrimination between bands of infrared radiation. By pairing different optical antenna dyes to specific nanoparticle compositions, unique visible emission is associated with different bands of infrared excitation. In one material set, the peak emission was increased 10-fold, and the width of the spectral response was increased more than 10-fold.